The discovery of a potent series of carboxamide TRPA1 antagonists12. Issue 11 (7th September 2016) - Pryde, D. C.; Marron, B.; West, C. G.; Reister, S.; Amato, G.; Yoger, K.; Padilla, K.; Turner, J.; Swain, N. A.; Cox, P. J.; Skerratt, S. E.; Ryckmans, T.; et al.
Abstract : Potent and selective carboxamide TRPA1 antagonists were identified by high throughput screening, with efficacy demonstrated in a topical inflammation model. Abstract : A series of potent and selective carboxamide TRPA1 antagonists were identified by a high throughput screen. Structure–activity relationship studies around this series are described, resulting in a highly potent example of the series. Pharmacokinetic and skin flux data are presented for this compound. Efficacy was observed in a topical cinnamaldehyde flare study, providing a topical proof of pharmacology for this mechanism. These data suggest TRPA1 antagonism could be a viable mechanism to treat topical conditions such as atopic dermatitis.